PELATIHAN PENULISAN MAKALAH ILMIAH BAGI MAHASISWA SEMESTER II DIPLOMA III KEBIDANAN AL-MA’ARIF BATURAJA (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2022)
This Community Service activity aims to improve the understanding and ability of semester II Diploma III Midwifery students in writing scientific papers. Through this training activity, it is hoped that semester II Diploma III Midwifery students can add experience, understanding and also the ability to write scientific papers which will later be beneficial for students. This activity was attended by Diploma III Midwifery students. The methods used include lecture, discussion and simulation methods. This Community Service activity was held on October 4, 2022 in the Al-Ma'arif Baturaja Diploma III Midwifery class room. Based on the results of the activities that have been carried out, the enthusiasm of semester II Diploma III Midwifery students of Al-Ma'arif Baturaja in participating in activities so that students better understand the material about writing scientific papers